2019
DOI: 10.1002/smll.201900438
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Nanocrystal Self‐Assembly in Real Time Using In Situ Small‐Angle X‐Ray Scattering

Abstract: involve a variety of interactions and driving forces between inorganic hard core, organic soft surface-coating ligands, and surrounding solvent molecules. [2,[7][8][9] As a consequence, a thorough understanding of a solvent-mediated assembly process is required to produce NC solids with programmable properties.Here, we have chosen lead sulfide (PbS) nanocrystals as a model system for the investigation of the in situ self-assembly due to the possibility to produce monodisperse particles in a colloidal solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 43 publications
3
52
0
Order By: Relevance
“…The occurrence of the two SL types (rhcp and bcc) found here may be related to the previously observed hcp–bcc transition for OA‐capped PbS NC SLs upon tailored solvent evaporation. [ 29 ] Similarly, our polycrystalline bcc SLs are assembled from PbS NCs dispersed in hexane, whereas hexane‐octane mixtures resulted in monocrystalline rhcp SLs. This invokes different solvent evaporation rates, which may lead to distinct SL unit cells.…”
Section: Figurementioning
confidence: 93%
“…The occurrence of the two SL types (rhcp and bcc) found here may be related to the previously observed hcp–bcc transition for OA‐capped PbS NC SLs upon tailored solvent evaporation. [ 29 ] Similarly, our polycrystalline bcc SLs are assembled from PbS NCs dispersed in hexane, whereas hexane‐octane mixtures resulted in monocrystalline rhcp SLs. This invokes different solvent evaporation rates, which may lead to distinct SL unit cells.…”
Section: Figurementioning
confidence: 93%
“…Computer simulations showed that crystallization at such a low volume fraction is only possible if attractive interactions between colloidal nanoparticles are significant [96]. The evaporation induced self-assembly of lead sulfide (PbS) nanoparticles was studied by in situ SAXS [97]. The initial colloidal liquid ordered to a swollen hexagonal closed-packed (hcp) superstructure along the cell walls before transforming to bcc structure upon drying.…”
Section: In Situ Studies Of Nucleation and Growthmentioning
confidence: 99%
“…Still, despite the enormous success of SE, many fundamental questions are still unresolved, such as how much solvent (if any) remains in the final equilibrium structure, how the parameters controlling the evaporation process affect the quality of the final SLs, or the sequence of events and potential barriers that lead to crystallization. This includes identification of intermediate structures, such as an fcc to bcc (Bain) 14,15 or hcp to bcc 16 transition. Furthermore, it is well known 1 that SE and ST do not generally result in the same structures for the same conditions, raising issues related to metastability.…”
Section: Introductionmentioning
confidence: 99%
“…and Yang et al,11 all previous BNSLs have been obtained through heterogeneous nucleation, where crystallization occurs on a substrate. Recent experiments have began to characterize the dynamics of assembly14,16 in single component SLs, and establish that the final bcc SL proceeds through an intermediate fcc or hcp phase. In fact, the experiments in ref 16.…”
mentioning
confidence: 99%
See 1 more Smart Citation